PENGARUH PEMBERIAN KONSELING TERHADAP DEPRESI POST PARTUM DI PUSKESMAS II DAN IV DENPASAR SELATAN - Pamela Kenwa (Coping: Community of Publishing in Nursing, 2015)
Post partum depression is the changing of mother’s mood after labor because of many problem that had been around when she’s pregnant or after labor. Many therapy can be using for eliminate the incident of post partum depression such like counseling. This research aim to analyze the effect of counseling to post partum depression in Puskesmas II dan IV South Denpasar with study design was a Quasi Experiment post test with control group. The instrument used to measure post partum depression using the Edinburgh Postnatal Depression Scale (EPDS) which has been modificated by Soep. Based on test statistic Independent Sample T-Test, got the test significant p=0,04 (<0,05) indicating counseling have an effect to post partum depression in mothers.